Advanced Techniques of Malware Evasion and Bypass in the Age of Antivirus - Kausar Parveen (International Journal for Electronic Crime Investigation, 2024)
The use of antivirus software as the main line of protection against growing cyber threats highlights the necessity of comprehending and resolving its limits. This study provides light on the ease of use and accessibility of tools used by hackers by carefully examining the complex terrain of malware evasion and bypass tactics. The persistent evolution of malware evasion and bypass techniques presents a significant cybersecurity challenge. The main objective is to educate users about the ever-changing hazards and provide them with the knowledge they need to properly strengthen their digital defenses. The literature analysis highlights the necessity for continued attention by establishing a strong correlation between the effectiveness of evasion strategies and their age and popularity. While modern antivirus software shows strong resistance against a range of tried-and-true techniques when updated on a regular basis, the study reveals a crucial component in its testing. This entails applying simple yet effective tweaks to well-known evasion techniques, demonstrating their capacity to fool even the most recent antivirus software. A thorough examination of malware evasion tactics, including both on-desk and in-memory approaches, is given in the methods section. Packing, obfuscators, protectors, reflective DLL injection, remote process memory injection, process hollowing, and inline hooking are all covered in detail in this paper. Subsequently, the study delves deeper into distinct evasion strategies, such defensive evasion through direct system calls and sophisticated evasion tactics, showcasing malware developers’ versatility in evading antivirus and endpoint detection and response (EDR) systems.